Respuesta :
Hi there!
To convert an equation from standard form to slope-intercept form, you need to pull the x over to the other side by making it 0 (by either subtracting or adding that number on both sides):
4x + 2y = 10----> 2y = -4x + 10
Now, we simply divide both sides by the coefficient on y and there you have it!
y = -2x + 5
To convert an equation from standard form to slope-intercept form, you need to pull the x over to the other side by making it 0 (by either subtracting or adding that number on both sides):
4x + 2y = 10----> 2y = -4x + 10
Now, we simply divide both sides by the coefficient on y and there you have it!
y = -2x + 5
Step-by-step explanation:
Take example :-
- 2x + 4y -4 = 0
- 4y = -2x +4
- y = -1/2x + 1